Generation and Application of a Reporter Cell Line for the Quantitative Screen of Extracellular Vesicle Release - Shpigelman, Jonathan; Lao, Fitzgerald S.; Yao, Shiyin; Li, Chenyang; Saito, Tetsuya; Sato-Kaneko, Fumi; Nolan, John P.; Shukla, Nikunj M.; Pu, Minya; Messer, Karen; Cottam, Howard B.; Carson, Dennis A.; et al. (Frontiers in Pharmacology, 2021)
Extracellular vesicles (EVs) are identified as mediators of intercellular communication and cellular regulation. In the immune system, EVs play a role in antigen presentation as a part of cellular communication. To enable drug discovery and characterization of compounds that affect EV biogenesis, function, and release in immune cells, we developed and characterized a reporter cell line that allows the quantitation of EVs shed into culture media in phenotypic high-throughput screen (HTS) format. Tetraspanins CD63 and CD9 were previously reported to be enriched in EVs; hence, a construct with dual reporters consisting of CD63-Turbo-luciferase (Tluc) and CD9-Emerald green fluorescent protein (EmGFP) was engineered. This construct was transduced into the human monocytic leukemia cell line, THP-1. Cells expressing the highest EmGFP were sorted by flow cytometry as single cell, and clonal pools were expanded under antibiotic selection pressure. After 4 passages, the green fluorescence dimmed, and EV biogenesis was then tracked by luciferase activity in culture supernatants. The Tluc activities of EVs shed from CD63Tluc-CD9EmGFP reporter cells in the culture supernatant positively correlated with the concentrations of released EVs measured by nanoparticle tracking analysis. To examine the potential for use in HTS, we first miniaturized the assay into a robotic 384-well plate format. A 2210 commercial compound library (Maybridge) was then screened twice on separate days, for the induction of extracellular luciferase activity. The screening data showed high reproducibility on days 1 and 2 (78.6%), a wide signal window, and an excellent Z' factor (average of 2-day screen, and 0.54). One hundred eighty-seven compounds showed a response ratio that was 3SD above the negative controls in both day 1 and 2 screens and were considered as hit candidates (approximately 10%). Twenty-two out of 40 re-tested compounds were validated. These results indicate that the performance of CD63Tluc-CD9EmGFP reporter cells is reliable, reproducible, robust, and feasible for HTS of compounds that regulate EV release by the immune cells.